Oviposition Deterrent of Bactrocera carambolae Resulted from Eggs Deposition on Mango - Muryati Muryati; Y. Andi Trisyono; Witjaksono Witjaksono; Wahyono Wahyono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Oviposition deterrent is chemical compounds which are used for avoiding eggs deposition. The oviposition deterrent resulted from eggs deposition is valuable information that can be manipulated for managing its population. The objective of this research was to determine the presence of oviposition deterrent resulted by female Bactrocera carambolae on mango. Extraction of oviposition deterrent was conducted by maceration method. The preference test was performed using two arms olfactometer, meanwhile the oviposition deterrent test was conducted by exposed gravid females to fruit that already smeared with extracts. The result revealed that gravid females of B. carambolae were attracted to methanol extract of 1 day after egg deposition, whereas the methanol extract of 3 and 5 days after egg deposition repelled gravid females. Oviposition deterrent test indicated that methanol extract at category 3 and 5 acted as a deterrent. The preference of gravid females of B. carambolae to different category of infested fruit extracts was probably influenced by the chemicals modification on mango after oviposition. This result suggested that the female B. carambolae do not deposit oviposition deterrent. The phenomenon of deterrence was probably as a result of chemical changes in fruit as a consequence of eggs infestation.